Determinants of Timeliness of Submission of Financial Reports - Nyimas Anandhita Jasmine Nabila; Siti Nur Hadiyati (Rescollacom (Research Collaborations Community), 2026)
Timely submission of financial statements is a crucial aspect of financial reporting quality and capital market transparency, as it reduces information asymmetry and supports informed decision-making by investors and regulators. Despite clear regulatory deadlines in Indonesia, delays in financial report submission remain a recurring issue, particularly among publicly listed companies. This study aims to examine the determinants of the timeliness of annual financial report submission by focusing on firm size, ownership structure, firm age, leverage, and profitability. The research specifically investigates food and beverage companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This study employs a quantitative associative research design using secondary data obtained from audited annual reports. A purposive sampling method was applied, resulting in 114 firm-year observations. Data analysis was conducted using multiple linear regression, supported by classical assumption tests to ensure the robustness of the model. Hypothesis testing was performed using partial t-tests to evaluate the individual effect of each independent variable on reporting timeliness. The results indicate that firm size, leverage, and profitability have a significant positive effect on the timeliness of financial report submission. Larger firms tend to report more promptly due to stronger external monitoring and better internal resources. High leverage increases pressure from creditors, encouraging timely disclosure, while profitable firms are motivated to quickly report positive performance. In contrast, ownership structure and firm age do not show a significant influence on reporting timeliness. These findings suggest that financial characteristics play a more dominant role than organizational attributes in determining reporting punctuality. The study provides practical implications for regulators and stakeholders in improving compliance with financial reporting deadlines.